If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20z + 1 = 24z + 7 Reorder the terms: 1 + 20z = 24z + 7 Reorder the terms: 1 + 20z = 7 + 24z Solving 1 + 20z = 7 + 24z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-24z' to each side of the equation. 1 + 20z + -24z = 7 + 24z + -24z Combine like terms: 20z + -24z = -4z 1 + -4z = 7 + 24z + -24z Combine like terms: 24z + -24z = 0 1 + -4z = 7 + 0 1 + -4z = 7 Add '-1' to each side of the equation. 1 + -1 + -4z = 7 + -1 Combine like terms: 1 + -1 = 0 0 + -4z = 7 + -1 -4z = 7 + -1 Combine like terms: 7 + -1 = 6 -4z = 6 Divide each side by '-4'. z = -1.5 Simplifying z = -1.5
| -7-5x+4=-24x+18-5x | | (2x+10)+(x-10)+(2x-20)=180 | | (9x+24)=(6+66) | | -4x^2=8x-3 | | (X+30)+(2x)+(3x-30)=180 | | 12x-11x-2=-4 | | 2x^3-6x^2+4x-12=0 | | 7(x+7)=30 | | 6y=3.5 | | (2x)+(x+10)+(3x-10)=180 | | -9+2=-16 | | 5(x+4)+5=1 | | -3x-1.5y=0 | | 8y-12=6+2(10y-3) | | 2/3=k/9 | | 4/3=24/r | | 4/3=23/r | | 4x^2+8=10 | | -2(x+2)-4(x-3)=22 | | X+86+35+63+x=180 | | (2x)+(x+10)+(3x-7)=180 | | 3x=3.84 | | -5t-4(2+2t)=-4 | | 4+5u=9 | | 2x(x+1)+9=(3x+1)(x-1) | | 6(2m-8)=36 | | -30m^3n^4-5m^4=0 | | (4m+t)= | | X^2-is+100=0 | | y=1/2x-4/3 | | 7y-18=-4 | | 3x^2-15x-35=0 |